Time‐series transcriptomics reveals a drought‐responsive temporal network and crosstalk between drought stress and the circadian clock in foxtail millet. (4th April 2022) - Yi, Fei; Huo, Mingyue; Li, Jianrui; Yu, Jingjuan
SUMMARY: Drought stress is a serious factor affecting crop growth and production worldwide. The circadian clock has been identified as key to improving regional adaptability of plants. However, our understanding of the contribution of the circadian clock to drought response and the impacts of drought stress on the circadian clock in plants is still limited. To explore the interactions between the circadian clock and drought stress, foxtail millet seedlings were treated with simulated drought (20% polyethylene glycol‐6000) treatment starting at the day (DD) onset zeitgeber time 0 (ZT0, lights on) and at the night (DN) onset zeitgeber time 16 (ZT16, lights off). A high temporal‐resolution transcriptomic investigation was performed using DD and DN samples collected at intervals of 2 or 4 h within a 24‐h drought‐treatment period. Overall, we identified 13 294 drought‐responsive genes (DRGs). Among these DRGs, 7931 were common between DD and DN samples, 2638 were specific to DD, and 2725 were specific to DN. Additionally, we identified 1257 circadian genes, of which 67% were DRGs. Interestingly, with drought treatment starting at the day for 8, 12 or 16 h, the circadian phase shifted to 12 h. We also found that the circadian clock led to different day and night drought‐responsive pathways. The identification of DRG_Clock (DRG and circadian clock) and DRG_NonClock (DRG and not circadian clock) genes provides a reference for selecting candidate drought resistance genes. Our work reveals the temporal drought‐response process and crosstalk between drought stress and the circadian clock in foxtail millet. Significance Statement: Our dataset provides a 24‐h temporal network of drought‐responsive genes based on two different drought treatment methods (drought starting at the day and starting at night, respectively) and reveals crosstalk between drought stress and the circadian clock in foxtail millet. In addition, the identification of DRG_Clock and DRG_NonClock genes that respond to drought provides a reference for researchers when selecting candidate drought‐resistant genes in the future.